1991
DOI: 10.1042/cs0810515
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood pressure during the normal menstrual cycle

Abstract: 1. Changes in blood pressure during the normal menstrual cycle are not well documented, and previous studies have given conflicting results. 2. Thirty normotensive women and ten mildly hypertensive women measured their blood pressure at home each morning for 6 weeks, under standardized conditions, using a UA-751 semi-automatic sphygmomanometer. All had normal menstrual cycles and subjects entered the study at difference phases of the cycle. 3. Blood pressure was higher at the onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 1 publication
5
67
0
Order By: Relevance
“…Journal of Human Hypertension in agreement with the hypothesis that oestrogen deprivation, either at the onset of menstruation 27 or in non-substituted postmenopausal normotensive [23][24][25] or hypertensive 22 women, may increase blood pressure. Oestrogens change the loading conditions on the elastin or collagen fibres or alter the structure of the vessel wall.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Journal of Human Hypertension in agreement with the hypothesis that oestrogen deprivation, either at the onset of menstruation 27 or in non-substituted postmenopausal normotensive [23][24][25] or hypertensive 22 women, may increase blood pressure. Oestrogens change the loading conditions on the elastin or collagen fibres or alter the structure of the vessel wall.…”
Section: Discussionsupporting
confidence: 86%
“…18 Other studies are in keeping with our findings, but did not correct for the level of blood pressure [19][20][21] or reported that withdrawal of hormonal replacement therapy for 4 weeks resulted in a decrease of systemic arterial compliance and an increase in pulse wave velocity in the femoralisdorsalis pedis region, but not in the aorto-femoral territory. 21 Recent studies using ambulatory monitoring [22][23][24][25][26] or automated blood pressure self-measurement 27 are…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As our meta-analysis included studies with participants spanning pubertal development, this may offer further explanation for the heterogeneity in the female subgroup, as major changes in oestrogen profile occur during the pubertal period. Furthermore, the menstrual cycle influences BP [51], and no studies reported controlling for menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have demonstrated that BP is lower when E 2 levels peak during the luteal phase than when they are at their nadir during the follicular phase of the menstrual cycle (Dunne et al, 1991;Karpanou et al, 1993;Chapman et al, 1997). Menopause is associated with a significant increase in BP in cross-sectional studies (Staessen et al, 1998).…”
Section: Estrogen Receptorsmentioning
confidence: 99%